Facultad de Ciencias Administrativas realizó jornada académica de casos prácticos del Examen Complexivo - García, Mariana (2023)
The Faculty of Administrative Sciences, Business Management and Informatics, comply with the agenda of Defense of Practical Cases, of the Accounting and Auditing, Business Administration, Tourism and Hospitality, Marketing, Software and Communication careers, works that were well raised and defended before the three courts that the faculty put together for the development of this academic activity, so that on January 25, 26 and 27, 2023, the gentlemen were examined on a double day students.